Respuesta :
Answer:
[tex]x =-24[/tex]
Step-by-step explanation:
Given
[tex](\frac{2}{3})(\frac{1}{2}x + 12) = (\frac{1}{2})(\frac{1}{3}x + 14) - 3[/tex]
Required
Solve for x
[tex](\frac{2}{3})(\frac{1}{2}x + 12) = (\frac{1}{2})(\frac{1}{3}x + 14) - 3[/tex]
Open all brackets
[tex]\frac{2}{3}*\frac{1}{2}x + \frac{2}{3}*12 = \frac{1}{2}*\frac{1}{3}x + \frac{1}{2}*14 - 3[/tex]
[tex]\frac{2 * 1}{3 *2}x + \frac{2 * 12}{3}= \frac{1 * 1}{2 * 3}x + \frac{1 * 14}{2} - 3[/tex]
[tex]\frac{1}{3}x + \frac{24}{3}= \frac{1}{6}x + \frac{14}{2} - 3[/tex]
[tex]\frac{1}{3}x +8= \frac{1}{6}x + 7 - 3[/tex]
Collect like terms
[tex]\frac{1}{3}x - \frac{1}{6}x =7 - 3 -8[/tex]
[tex]\frac{1}{3}x - \frac{1}{6}x =-4[/tex]
Solve fraction
[tex]\frac{2-1}{6}x =-4[/tex]
[tex]\frac{1}{6}x =-4[/tex]
Multiply both sides by 6
[tex]6 * \frac{1}{6}x =-4 * 6[/tex]
[tex]x =-4 * 6[/tex]
[tex]x =-24[/tex]
Answer:
Step-by-step explanation:
Given
Required
Solve for x
Open all brackets
Collect like terms
Solve fraction
Multiply both sides by 6